2023
DOI: 10.3389/fpsyg.2023.1153339
|View full text |Cite
|
Sign up to set email alerts
|

EFL teachers’ digital literacy: the role of contextual factors in their literacy development

Abstract: IntroductionDigital technology can have significant effects on language education. This effect makes the English language teachers teach the subjects better to the students and also improves the quality of teachers’ education.MethodsThe purpose of this research is to evaluate the digital literacy of English language teachers and to investigate the difference between digital literacy and their gender, education level, and teaching experience. To conduct the study, the researcher invited 2,110 EFL teachers to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
4
1
Order By: Relevance
“…Additionally, Antuñano et al (2022) add that based on their findings, teachers' knowledge and skills in digital use will vary in terms of age, degree, and educational background with teaching. However, these results contradict Zhang (2023), who found that age, gender, education level, and teaching experience are not related to digital literacy abilities. The high or low level of teachers' literacy skills can be influenced by their confidence levels in using digital devices (Siyam, 2019).…”
Section: Teacher Leaders Literacycontrasting
confidence: 79%
“…Additionally, Antuñano et al (2022) add that based on their findings, teachers' knowledge and skills in digital use will vary in terms of age, degree, and educational background with teaching. However, these results contradict Zhang (2023), who found that age, gender, education level, and teaching experience are not related to digital literacy abilities. The high or low level of teachers' literacy skills can be influenced by their confidence levels in using digital devices (Siyam, 2019).…”
Section: Teacher Leaders Literacycontrasting
confidence: 79%
“…Zhang provides insights into the digital literacy of English language teachers by investigating variances associated with gender, education level, and teaching experience, thus offering a perspective on the influence of contextual factors on literacy development. [15] [16] In light of the current state of digital literacy among international Chinese teachers, implementing comprehensive and multifaceted strategies to promote their digital transformation has become an urgent need in the field of education. This transformation process relies not only on the policy support and guidance of educational administrative departments but also on the innovative drive of educational technology companies, the in-depth research and support of academic institutions, and the teachers' personal active exploration and application of new technologies.…”
Section: [3][4][5]mentioning
confidence: 99%
“…Teachers' attitude towards technology directly impacts its use and successful integration [94]. Further, it is claimed that digital literacy is significantly influenced by the teacher's attitude over other contextual factors such as education level, gender, and experience [95]. Teachers, in general, possess a positive attitude towards technologyenhanced teaching [22,36,38,48,50,53,62].…”
Section: Teacher's Attitudes and Motivation Towards Technology Enhanc...mentioning
confidence: 99%